(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article provides information on the number of tubers formed at the root of a plant when mineral fertilizers are applied at different rates when treating Orzu soybean seeds with nitragin, grown as a secondary crop.